Childhood maltreatment and aggressive behavior among college students: a serial mediation model of authenticity and alexithymia - Zhou, Jingya; Wei, Meiting; Xie, Qing (Frontiers in Psychiatry, 2024)
Aggressive behavior among college students jeopardizes the mental health and personal development of both the aggressors and the victims, and undermines societal stability. Previous research confirms a positive relationship between childhood maltreatment and aggressive behavior, but the underlying mechanisms still warrant further exploration. Our study investigated the impact of childhood maltreatment on aggressive behavior among college students, as well as the mediating roles of authenticity and alexithymia. An online survey was administered to 1,148 Chinese college students using the Childhood Trauma Questionnaire-Short Form (CTQ-SF), Authenticity Scale, Toronto Alexithymia Scale (TAS-20), and 12-item Aggression Questionnaire (12-AQ). The results indicate that: 1) Authenticity and alexithymia each mediated the positive relationship between childhood maltreatment and aggressive behavior. The mediating effect of authenticity was 0.04 (95% CI [0.01, 0.06]), and that of alexithymia was 0.10 (95% CI [0.07, 0.13]). 2) A chain-mediating effect involving authenticity and alexithymia was observed (with a chain-mediating effect of 0.03, 95% CI [0.02, 0.05]). This study shows that childhood maltreatment can positively predict aggressive behavior in college students, and this effect is mediated individually and sequentially by authenticity and alexithymia. Our findings contribute to the body of research in this domain and offer a theoretical framework for interventions aimed at reducing aggressive behaviors among college students.